The Mental Health in Austrian Teenagers (MHAT) Study: design, methodology, description of study population - Zeiler, Michael (Neuropsychiatr, 2018)
Profound epidemiological data on the prevalence of mental health disorders and respective risk and protective factors is a prerequisite for adequate prevention, intervention and service planning. Children and adolescents are regarded as high priority groups for prevention in this field because of the high chronicity and individual burden of mental health disorders. The Mental Health in Austrian Teenagers (MHAT)-Study is the first epidemiological study based on a large representative sample of adolescents (N > 3700) in Austria in order to obtain the prevalence of a wide range of behavioral problems and psychiatric disorders. Adolescents are recruited from multiple settings (schools, course providers for early school leavers and psychiatric clinics) in order to enhance the representativity of the sample. A “gold-standard” two-stage design (screening questionnaire and diagnostic interviews) is used to obtain psychiatric diagnoses that are based on the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders which was published by the American Psychiatric Association in 2013. This paper aims at presenting the study design and methodology of the MHAT study, describing the study population as well as discussing relevant strengths and limitations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40211-018-0273-2) contains supplementary material, which is available to authorized users.